Best Investments for an Economic Recovery from Coronavirus : An Illustration Based on the Fiji Climate Vulnerability Assessment to Pinpoint Stimulus Options - Fargher, Samuel; Hallegatte, Stephane (World Bank, Washington, DC, 2020)
The COVID-19 crisis is causing massive suffering across the globe. In addition to the human consequences of the disease, containment measures to slow down and control the virus have deprived people of their livelihood and put many firms in a difficult financial situation. As a result, governments are planning massive stimulus packages to accelerate recovery once the health emergency is under control. To help governments think through investments for a green recovery, we proposed a sustainability checklist to screen potential projects and policies. To test how the sustainability checklist might work for a specific country, the checklist was applied to the Fiji Climate Vulnerability Assessment (CVA). The objective is to demonstrate how the checklist can be used as a screening, scoring, and prioritization tool to identify projects that create synergies between short-term needs and long-term objectives.